Grounds for invalidating the debtor’s transactions during the rehabilitation and bankruptcy procedur - Kopzhasarova, S.I. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of the study is to comprehensively analyze objective and subjective suspicious transactions within the framework of the grounds for rehabilitation and invalidation of bankruptcy transactions, to consider their historical aspect, to focus on gaps in domestic legislation, to conduct a comparative analysis with foreign legislation. The methodological basis of the research consists of general and separate methods, such as formal-logical, scientific analysis and synthesis, comparative-legal, historical-legal. As a result of the study, the historical aspect of challenging the transaction in bankruptcy was considered, that is, the institutions of ancient Roman law “Actio Pauliana” – Paulian lawsuit, “Laesio enormis”. A legal analysis of the provisions of Article 7, paragraph 2, subparagraphs 1) and 3) of the Law of the Republic of Kazakhstan “On Rehabilitation and Bankruptcy” was carried out, and the author’s conclusions were given regarding opinions related to the concept of “significantly different for the worse”. By conducting a comparative analysis of the bankruptcy legislation of the Republic of Kazakhstan and the Russian Federation, the features of objective and subjective suspicious transactions are considered and examples from judicial practice are given. Various views on the use of objective and subjective theories in invalidating bankruptcy transactions are discussed. In conclusion, suggestions are made that in order to form a unified judicial practice, it is necessary to clarify some concepts in the legislation of the Republic of Kazakhstan On bankruptcy.